Tem palhaça na rua-rio? Tem sinsinhô! : Vivências de palhaçaria e educação popular no Porto do Sal - LIMA, Alana Clemente (Universidade Federal do Pará, 2019)
It has the clown on the street-river? Yes, it has sir is a research-literary that investigates the relationship between the clowning and the practice of popular education in the context of the Ter.Ser project, art and popular education, developed in the community of Porto do Sal, in the neighborhood of Cidade Velha in Belém do Pará. The project, social, artistic and political, is organized through a popular school with regular activities in the community and specific artistic-political interventions. The research, based on the phenomenology of Gaston Bachelard and on the phenomenology of the look of Alfredo Bosi, is structured as bibliographical and field, immersing in the poetic work of Manoel de Barros and in the literary work Peter Pan for the construction of the literary-scientific writing. I start from my trajectory as an educator-researcher-clown and I go through these three looks to discuss the experiences of the research, since I position myself as a researcher-participant. The work is divided into three notebooks driven by three guiding verbs: look, play and hope. These verbs and notebooks are interdependent and interconnected by narrative writing that always establishes continuity, bringing direct references to the work of James Barrie - Peter Pan - from the summary to the final considerations of the work. In the initial considerations - In search of the land of never - I contextualize my trajectory from the relationship with the play, presenting the elements of the work of Barrie and Manoel de Barros that talk with the research and in this context I invite the reader to fly with me in this search. In the notebook 1 - Look, titled The second to the right, then direct until tomorrow morning, I present the perspective of the three looks that I assume in the research, educator-researcher, bringing the poetic and real images constructed from the contact with the community of the Porto do Sal, is the presentation book of the place and the educational practice of the project, where he studied in. In the notebook 2 - Playing, titled Powder of pirlimpimpim, I cross the births of my clown Xulipa Margarida and the relation with the play, the game, the clownery and the theater of invasion, looking for references of Alice Viveiros de Castro, Marton Maués, Romana Melo , Andréa Flores, André Carreira, Johan Huizinga, and Tizuko Kishimoto. The notebook 3 – To Hope, also called With a little fairy dust the lost girl begins to fly, brings the flight of the educator-researcher clown to the land of never and to the universe of the clowning and popular education in the community of the Port of Sal Interlacing theory and stories of experiences, it is the notebook that builds the crossings of all the way of the flight until here. In the place of the final considerations, Since all this happened a long time ago, the reflections on the experiences, the popular education and the production of knowledge in arts organize in this point, that intends to always leave the window open for the flight from the many neverlands always exist. From this, close your eyes, think of good things that the powder of pirlimpimpim will show us the way!